1990
DOI: 10.1002/j.2161-1874.1990.tb00199.x
|View full text |Cite
|
Sign up to set email alerts
|

Substance Abuse Counseling in Community Corrections: A Primer

Abstract: Substance abuse counseling treatment in community corrections ultimately aims to assist offenders in learning constructive coping skills and restoring social and occupational functioning. A review is discussed of various treatment methods that have survived the tests of empirical scrutiny, clinical experience, and practical financial considerations. In addition, these methods are offered for consideration by community corrections professionals in developing a basic design for outpatient substance abuse treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The two treatment programs that were the focus of this study contain most of the treatment components that researchers have found to be effective interventions in community-based substance abuse programs for offenders (Harland, 1996;74 JOURNAL OF OFFENDER REHABILITATION l Haddock, 1992). For quite some time, the literature has suggested that an optimal length of treatment for addicted offenders is somewhere in the range of 18 months (Martin, Butzin, & Inciardi, 1995;Wexler, 1995;Hooper, Lockwood, & Inciardi, 1993;Martin & Inciardi, 1993;Inciardi et al, 1992;Lipton, 1989;McClellan et al, 1981).…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…The two treatment programs that were the focus of this study contain most of the treatment components that researchers have found to be effective interventions in community-based substance abuse programs for offenders (Harland, 1996;74 JOURNAL OF OFFENDER REHABILITATION l Haddock, 1992). For quite some time, the literature has suggested that an optimal length of treatment for addicted offenders is somewhere in the range of 18 months (Martin, Butzin, & Inciardi, 1995;Wexler, 1995;Hooper, Lockwood, & Inciardi, 1993;Martin & Inciardi, 1993;Inciardi et al, 1992;Lipton, 1989;McClellan et al, 1981).…”
Section: Implications For Future Researchmentioning
confidence: 99%